The Philippines: Origins to the End of the Pleistocene - Pawlik, Alfred (Archīum Ateneo, 2024)
The recent discovery of an in-situ disarticulated skeleton of a Rhinoceros philippinensis with traces of butchering and associated stone tools have established a date for the earliest colonization of the Philippines by a hominin species to at least 700,000 years ago. This unequivocal evidence for a hominin presence in the Philippines supports previous claims from scattered lithics assemblages in both the northern and southern Philippines for a Lower Palaeolithic occupation of the islands. The discovery of fossil remains of Homo luzonensis in Callao Cave indicates that hominins lived on the island of Luzon until at least 67–50 kya. Anatomically modern humans (AMH) were clearly present in the Philippines by c.40 kya and could potentially have reached the region considerably earlier. The Late Pleistocene archaeological record of the Philippines suggests AMH arrived on the islands with the pre-existing knowledge and technological sophistication to take advantage of the new and varied environments as they dispersed across Island Southeast Asia as far as Australasia. Over the succeeding millennia, the inhabitants of different islands and archipelagos independently innovated technologies in a variety of raw materials. Towards the end of the Pleistocene new ideologies emerged, and there is evidence for increasing mobility and contact between human populations across regional seascapes.